Exploring the Impact of Low-Concentration Atropine Eye Drops on the Progression of Myopia: A Systematic Review: Oral Presentation - Observational Study - General practitioner - Stella Nathania; Gabriella Hafidha Badruddin; Jovita Jutamulia (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Low-concentration atropine eye drops have emerged as a promising therapy for the management of myopia. However, the effectiveness of atropine for myopia has not been widely studied. This paper aims to analyze the efficacy of low-concentration atropine eye drops for progression of myopia. Methods : A comprehensive literature search was performed on 3 online databases: PubMed, Cochrane, and ProQuest. We used 'Low-concentration atropine eye drops’, ‘Atropine’, ‘Eye Drops’, ‘Myopia’, and their MeSH terms as keywords. All studies included in analysis were available in English and full text format. We analyzed children myopia progression rates from all studies. We used Rayyan, an online-based tool, to conduct the screening process. Results : Three randomized control trials (RCTs), two cohort studies, and three case report studies with a total of 1389 participants were analyzed. Most studies were done in Asia, except one RCT in Australia. The participants range from 4-12 years old. Atropine eye drops concentrations that had been used were 0,01%, 0,025%, 0,05%, 0,1%, 0,125%, and 0,2%. All studies showed slower progression rate of myopia compared to the control group (-0,31 D vs -0,90 D; -0,05 D vs -1,05 D; -0,27 D vs -0,81 D; -0,28 D vs -0,54 D; -0,18 D vs -0,45 D;−0.31 D vs −0.76 D; -0.91 vs -1.00 D; -0,38D vs -0,55 D) with P < 0,05, except one study P = 0,94. Conclusion : Low-concentration atropine eye drops have shown promising effects in slowing progression of myopia. However, further research is needed, particularly in non-Asian countries.